GipNet – Baseline Environmental Data Gathering and Measurement Technology Validation for Nearshore Marine Carbon Storage. (July 2017) - Hoffman, Nick; Hardman-Mountford, Nick; Jenkins, Charles; Rayner, Peter J.; Gibson, Gary; Sandiford, Mike
Abstract: The GipNet assets are the foundation to research programs for observations and instrument tests aimed at defining practical and relevant shallow-marine Measurement, Monitoring, and Verification (MMV) programs as the CCS industry considers shallow offshore waters in the Gulf of Mexico and other basins, as well as meeting the specifics of CarbonNet Project options. The CarbonNet Project is investigating large volume storage (nominal 125 million tonnes of CO2 over 25 years) in shallow waters within 20 km of the coastline, offshore Gippsland Australia. GipNet will research the levels of various types of noise and natural variation against which one seeks to detect a positive signal, or confirm a null signal. In the well-understood, high quality and thick reservoirs of the Gippsland Basin, plumes are expected to be very predictable, relatively thick, and easily observable with the right techniques such as timelapse 3D seismic imaging and downhole monitoring, but provision must also be made for unexpected outcomes and technologies sought that have low detection thresholds to identify thin or diffuse plume offshoots or early warning of unexpected plume movements in order to provide assurance of storage security. CarbonNet seeks to validate at this pre-commercial stage, an appropriate, but not excessive, range of measurements to characterise the pre-existing environments. For each proposed technology, the physics of detection was reviewed, as well as the practicalities of deployment in the shallow-water and nearshore environment with multiple sources of 'noise', of initial research and test instruments and later detection systems appropriate for a commercial project. Most importantly, each MMV technology was assessed for its value in monitoring CO2 storage Integrity, Conformance and Assurance and adding to the proven technologies of 3D seismic and downhole monitoring. Three key technologies were identified for trial deployments and further testing: 1. Natural Seismicity Monitoring Network 2. Atmospheric Monitoring 3. Baseline Marine Monitoring In determining funding, the physics of detection for each proposed technology was reviewed, as well as the practicalities of deployment in the shallow-water and nearshore environment with multiple sources of 'noise', of initial research and test instruments and later detection systems appropriate for a commercial project. Most importantly, each technology was assessed for their value in monitoring CO2 storage Integrity, Conformance and Assurance.